2021
DOI: 10.3389/fphar.2021.608971
|View full text |Cite
|
Sign up to set email alerts
|

Changing Patient and Public Beliefs About Antimicrobials and Antimicrobial Resistance (AMR) Using a Brief Digital Intervention

Abstract: Background: A key driver of antimicrobial resistance (AMR) is patient demand for unnecessary antibiotics, which is driven by patients’ beliefs about antibiotics and AMR. Few interventions have targeted beliefs to reduce inappropriate demand.Objective: To examine whether a brief, online algorithm-based intervention can change beliefs that may lead to inappropriate antibiotic demand (i.e. perceptions of antibiotic necessity and lack of concern about antibiotic harm).Design: Pre- and post-intervention study.Parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Interventions founded on psychology and health behaviour change principles have been shown successful in prompting behaviour change. 32 The HBM model has previously been used in veterinary research assessing owner compliance with diet recommendations, 33 demonstrating the adaptability of this tool to veterinary medicine. This study represents the first time the HBM has been applied to antibiotic use in the companion animal setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interventions founded on psychology and health behaviour change principles have been shown successful in prompting behaviour change. 32 The HBM model has previously been used in veterinary research assessing owner compliance with diet recommendations, 33 demonstrating the adaptability of this tool to veterinary medicine. This study represents the first time the HBM has been applied to antibiotic use in the companion animal setting.…”
Section: Discussionmentioning
confidence: 99%
“… 43 Similar to other behaviour change interventions, the animation was designed to discourage requests for antimicrobials by emphasizing the threat and consequences of AMR. 32 , 44 Scores for pet owners in the animation group indicated that they would be less likely to expect or request antimicrobials if their pet had diarrhoea (statements 8 and 19), would be prepared to wait longer before considering antimicrobial use (statement 16) and would also be more likely to consider delayed prescription of antimicrobials (statement 10). There was also a demonstration of greater awareness that requesting antimicrobials could increase unnecessary use (statement 12).…”
Section: Discussionmentioning
confidence: 99%
“…34,35 The participants read online scientific journals (78.2%) as a major information source on antibiotic therapy and resistance. 36…”
Section: Discussionmentioning
confidence: 99%
“…Explanation personalization was also addressed in this dimension. The authors of [77] showed that a personalized online algorithm-based intervention can change beliefs that may lead to inappropriate antibiotic demand by patients. Conversely, results obtained in [75] show that personalization enhances user experience, but the so-called "filter bubbles" favor the emergence of opinion polarization and radicalization through confirmation bias.…”
Section: Domain-specific Dimension As Shown In Tablementioning
confidence: 99%